2022
DOI: 10.3390/pathogens11040429
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Coxiella burnetii Cattle Abortion: A One-Year Observational Study

Abstract: Q fever is a zoonosis occurring worldwide in livestock. Often neglected in differential diagnoses, Q fever can persist in herds causing financial losses. In ruminants, well-known manifestations of Q fever are metritis, infertility, abortion, stillbirth and delivery of a weak or premature calf. In cattle, Q fever is frequently asymptomatic and/or under-reported. Few studies are available on the diagnosis of Coxiella burnetii as a cause of abortion in cattle using polymerase chain reaction (PCR) for pathogen det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…This prevalence suggests a high circulation of this bacterium in Belgium. Recently, 8.5% of Belgian bovine abortions originating from Wallonia, were tested positive for C. burnetii on the basis of a PCR test on a pool of fetal spleen and, if available, placental cotelydones (Saegerman et al, 2022). In Flanders, a percentage of only 1.5 % of bovine cases tested positive for C. burnetii.…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence suggests a high circulation of this bacterium in Belgium. Recently, 8.5% of Belgian bovine abortions originating from Wallonia, were tested positive for C. burnetii on the basis of a PCR test on a pool of fetal spleen and, if available, placental cotelydones (Saegerman et al, 2022). In Flanders, a percentage of only 1.5 % of bovine cases tested positive for C. burnetii.…”
Section: Discussionmentioning
confidence: 99%
“…The type of strain involved in infected livestock is a possible factor affecting clinical outcomes [4]. In recent years, the pathogen has been considered as the etiological agent of approximately 10% of abortions reported in cattle in various studies performed in different countries, e.g., Belgium, Italy, Brazil, and others [5][6][7]. A large study performed previously [8] showed that the main shedding routes in cattle are via the milk and vaginal mucus.…”
Section: Introductionmentioning
confidence: 99%
“…Coxiella burnetii is a bacterium that causes Q fever in humans [ 1 , 2 ] and coxiellosis in animals [ 3 , 4 ]. Transmission is primarily through inhalation of dry aerosol particles from infected animals although tick associated transmission has also been reported in animals [ 5 ].…”
Section: Introductionmentioning
confidence: 99%